2019
DOI: 10.3897/neobiota.51.36838
|View full text |Cite
|
Sign up to set email alerts
|

Soil solarization based on natural soil moisture: a practical approach for reducing the seed bank of invasive plants in wetlands

Abstract: Soil solarization is a well-established method to disinfect soil for efficient weed control. However, the feasibility of applying this method in the restoration of invaded natural habitats is unclear. This is because soil moisture is necessary for the success of solarization, but pre-irrigation in natural ecosystems is often not applicable, or demands high labor investment, making it unsuitable for use in restoration. The present study was based on the idea that the relatively high soil moisture in wetlands mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…At 40 DAS, total weed density was found lowest under mechanical weeding at 25 DAS + HW at 50 DAS and was statistically identical with 2 HW at 25 and 50 DAS, followed by soil solarization with 25 μm transparent polythene sheet + HW at 40 DAS, and the highest under application of Indian mustard oil cake @ 5 t/ha + HW at 40 DAS. Soil solarization is a hydrothermal method of weed management in which solar energy of sunlight is trapped under the transparent polyethylene sheet (Cohen et al, 2019). The solar energy increases the temperature of the soil, and weed seed loses its viability.…”
Section: Weed Density and Weed-control Efficiencymentioning
confidence: 99%
“…At 40 DAS, total weed density was found lowest under mechanical weeding at 25 DAS + HW at 50 DAS and was statistically identical with 2 HW at 25 and 50 DAS, followed by soil solarization with 25 μm transparent polythene sheet + HW at 40 DAS, and the highest under application of Indian mustard oil cake @ 5 t/ha + HW at 40 DAS. Soil solarization is a hydrothermal method of weed management in which solar energy of sunlight is trapped under the transparent polyethylene sheet (Cohen et al, 2019). The solar energy increases the temperature of the soil, and weed seed loses its viability.…”
Section: Weed Density and Weed-control Efficiencymentioning
confidence: 99%
“…Specifically, practitioners do have control over the timing of solarisation, which determines the magnitude of both temperature and solar radiationthe drivers responsible for raising the temperature of solarised soil. In contrast, practitioners typically do not have the option to artificially water or till the soil due to infrastructure and equipment limitations (Cohen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Solarization in turn has been employed by researchers such as Cohen et al (2019), who affirm the effectiveness of solarization in reducing the seed bank of various invasive trees, including Pereskia aculeata and Leucaena leucocephala. According to Fragoso et al (2016), it was observed in the field that soil solarization promoted greater control over (Megathyrsus maximus) colonião grass compared to (Cyperus rotundus) tiririca, however being efficient on the species studied.…”
Section: Introductionmentioning
confidence: 99%